2015
DOI: 10.1039/c5sm00654f
|View full text |Cite
|
Sign up to set email alerts
|

From coffee rings to coffee eyes

Abstract: We discuss how the stain left after evaporation of a suspension evolves with heating of the glass or plastic on which the liquid has been deposited. Upon increasing the substrate temperature, it is found that the stain gradually changes from the usually observed ring to an "eye" shape, that is, a combination of the thick central stain and the thin outer ring. Both the size and the relative volume of the central stain increase with the substrate temperature. The main mechanism for this phenomenon is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
145
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(163 citation statements)
references
References 41 publications
18
145
0
Order By: Relevance
“…The temperature gradient detected by an infrared technique was shown to orient to the contact line for both the natural and heating conditions, in consistent to the temperature profiles obtained by Girard,et al 37 . Subjected to the same mechanism that the inward Marangoni flow is enhanced upon heating the solid surface, the deposited profile transferred from a single ring to a dual ring formed by polystyrene spheres in the study of Li, et al 26 .…”
Section: Introductionmentioning
confidence: 96%
“…The temperature gradient detected by an infrared technique was shown to orient to the contact line for both the natural and heating conditions, in consistent to the temperature profiles obtained by Girard,et al 37 . Subjected to the same mechanism that the inward Marangoni flow is enhanced upon heating the solid surface, the deposited profile transferred from a single ring to a dual ring formed by polystyrene spheres in the study of Li, et al 26 .…”
Section: Introductionmentioning
confidence: 96%
“…They reported that the temperature difference between the contact line and the droplet apex decreases with time. Regarding colloidal suspensions, Li et al [12] reported the deposits obtained after evaporation of an aqueous droplet containing 0.25% (v/v) polystyrene nanoparticles on a glass substrate, heated from 30ºC to 80ºC. They reported that the "coffeering" changes to a "coffee-eye" due to inward axisymmetric Marangoni flow.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]. Nearly all data sets show that the skewness of the deposit reduces with increasing additives, indicating that pillars become flatter.…”
Section: Discussionmentioning
confidence: 91%
“…One of the aims of ongoing research into drying sessile droplets is to control and Contribution to the Topical Issue "Wetting and Drying: Physics and Pattern Formation", edited by Duyang Zang, Ludovic Pauchard and Wei Shen. a e-mail: david.fairhurst@ntu.ac.uk prevent the formation of the coffee ring-stain as many commercial processes require a uniform deposit. Several mechanisms have been observed to achieve this goal including: non-spherical particles [4], capillary forces [5]; Marangoni flow induced by surface tension gradients [6]; electrowetting [7]; using droplets smaller than a critical size [8] and heated substrates [9]. Many of these effects are summarised in a recent review [10].…”
Section: Introductionmentioning
confidence: 99%